Aβ aggregation behavior at interfaces with switchable wettability: a bioinspired perspective to understand amyloid formation. Issue 21 (15th February 2021) - Guan, Yijia; Yu, Dongqin; Sun, Hanjun; Ren, Jinsong; Qu, Xiaogang
Abstract : A PPy/TCA film was used as a model to show that the effect of dynamic wettability strongly influences amyloid formation. Abstract : An amphiphilic taurocholic acid (TCA) doped polypyrrole (PPy) film (PPy/TCA) was used as a dynamic mimic membrane model to explore how switchable surface wettability influences amyloid aggregation. Our results indicate that the hydrophobic surface, not the hydrophilic surface, plays important roles in Aβ40 adsorption and aggregation.